2022
DOI: 10.1101/2022.02.18.481052
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

D2 dopamine receptor expression, sensitivity to rewards, and reinforcement learning in a complex value-based decision-making task

Abstract: In the basal ganglia, different dopamine subtypes have opposing dynamics at post-synaptic receptors, with the ratio of D1 to D2 receptors determining the relative sensitivity to gains and losses, respectively, during value-based learning. This effective sensitivity to reward feedback interacts with phasic dopamine levels to determine the effectiveness of learning, particularly in dynamic feedback situations where frequency and magnitude of rewards need to be integrated over time to make optimal decisions. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…It has been suggested that the A1 allele is associated with a mutation in the promoter/regulatory gene element that decreases the D2 receptor expression. 56 , 57 Although this study did not measure the density of the D2 receptors in individuals carrying the A2 allele, other studies have linked high DA receptor density to people carrying the A2 allele. 58 Reuter et al 59 reported a high DA receptor density for people homologous for the A2 allele (hyperdopaminergic) and low receptor density associated with individuals carrying the A1 allele, 59 predicting that this may have an impact on the high behavioral approach system.…”
Section: Discussionmentioning
confidence: 89%
“…It has been suggested that the A1 allele is associated with a mutation in the promoter/regulatory gene element that decreases the D2 receptor expression. 56 , 57 Although this study did not measure the density of the D2 receptors in individuals carrying the A2 allele, other studies have linked high DA receptor density to people carrying the A2 allele. 58 Reuter et al 59 reported a high DA receptor density for people homologous for the A2 allele (hyperdopaminergic) and low receptor density associated with individuals carrying the A1 allele, 59 predicting that this may have an impact on the high behavioral approach system.…”
Section: Discussionmentioning
confidence: 89%